IMPLEMENTASI MEDIA APLIKASI KAMUS BERBASIS ANDROID DALAM PEMBELAJARAN KOSAKATA BAHASA ARAB DI MA MIFTAHUL FALAH CAPANG PURWODADI PASURUAN JAWA TIMUR - rochman, abd; Rokhmatulloh, Nur (Lugatuna : Jurnal Prodi PBA, 2024)
MA Miftahul Falah has Arabic language subjects, but many of the students are not enthusiastic about following the material provided by the teacher. In fact, there are still many class XI who are not interested in learning Arabic. Because the backgrounds of students are different.This study used a qualitative research design with participants from the MA Miftahul Falah school from a madrasa in the subdistrict area of Purwodadi Pasuruan. The Dictionary Application Media is implemented in learning Arabic Vocabulary for one academic semester. Data was collected through observation and interviews. Data analysis was performed using a qualitative descriptive approach.The results showed that the implementation of the Android-based Dictionary Application Media in Arabic Vocabulary learning had a positive impact that the implementation of the Dictionary Application Media in Vocabulary learning at MA Miftahul Falah had been carried out quite well, most of the students were enthusiastic in participating in learning.This study indicates that the Dictionary Application Media can be an effective alternative in learning Arabic Vocabulary. This media provides opportunities for students to actively participate in learning, increases social interaction between students, and strengthens their understanding of the subject matter.